Oxygen pressure and acid-base balance of mother and fetus during labor at high altitude - Sobrevilla, Luis (2015)
The oxygen tensión and acid-bases status of mother and fetus have been studied at delivery in 12 subjects from Lima (150 m.] and Cerro de Pasco (4,200 ,m.), Perú. Despite the low pO2 (60.7 ± 2 mm.Hg., x ± SEM) of maternal arterial blood at altitude, the tension of oxygen measured in microsamples of arterialized capillary blood from the fetal scalp was similar at altitude (19.0 ± 1.16 mm.Hg.) and sea level (21.5 ± 1.12 mm.Hg.). The fetus at altitude is born with a mixed acid-base disturbance that combines a respiratory alcalosis (pCO2 = 29.8 ± 3.4 mm.Hg.) with a metabolic acidosis (base-excess = -7.4 ± 1.6 m.Eq./L) and a pH similar to that found at sea level. The low fetal pCO2 correlotes welI with a decreased maternal pC02, at altitude, due to the additive effects of the hiperventilations of altitude and pregnancy (r = 0.77, p < 0 .001). There is a high degree of correlation between the maternal pCO2 and the fetal base-excess (r = 0.73, p < 0.001). Our findinqs indicate that the neonate at altitude is frecuently "small for dates", with the corresponding risks of congenital malformations, hipoglicemia and pulmonary pathology. They will thus have on important meaning on the observed increase in neonatal mortality at altitude.